Do Risk-Based Capital Requirements Allocate Financing and Cause a "Bigger" Loan Loss Provision for Islamic Banks? - Abdul Ghafar Ismail; Shahida Shahimi (Jurnal Iqtisad, 2003)
The purpose of the study is to examine the Islamic banks' response to the risk-based weighted capital requirements implemented in 1989. This paper will look at three possible effects; First, will the implementation of risk-based capital encourage substitution out as-sets in the 100 percent risk category such as deferred payment (debt contract) and, into as-sets in the less risky categories such as mudharabah and musharakah financing and gov-ernment investment certificates? Second, will the implementation of risk-based capital (RBC) discourage Islamic banks to utilize the equity financing upon subsidiary companies as the latter is deducted from the total capital base? Third, may the risk-based capital cause a "bigger" loan loss provision, as the concentration of financing is based on the debt contract? This study finds that Islamic banks could reduce financing portfolios in order to increase capital ratios. Second, the core capital ratio is enough to fulfill the 8% capital re-quirement indicating that Islamic banks do not rely on Tier-2 capital. Third, the higher percentage of debt financing may lead to the losses from debt financing that are entirely absorbed by banks and later, by depositors, resulting in lower return to depositors.   JEL Classification numbers: G15; G18; P51Keywords: Islamic banking; bank capital; loan loss provision